Prognostic Implications of the Immune Tumor Microenvironment in Patients With Pancreatic and Gastrointestinal Neuroendocrine Tumors. Issue 5 (May 2021) - Baretti, Marina; Zhu, Qingfeng; Zahurak, Marianna; Bhaijee, Feriyl; Xu, Haiying; Engle, Elizabeth L.; Kotte, Anil; Pawlik, Timothy M.; Anders, Robert A.; De Jesus-Acosta, Ana
Abstract : Objectives: The aim of this study was to characterize the tumor microenvironment of patients with gastroenteropancreatic neuroendocrine tumors relative to progression-free survival (PFS). Methods: Immune profiling for CD3, CD8, programmed death-1/programmed death-ligand 1, and indoleamine 2, 3-dioxygenase expression in 2 cohorts of gastroenteropancreatic neuroendocrine tumors: patients with short PFS (<4 years, n = 12) versus long PFS (≥4 years, n = 14) after surgery. Immune infiltrates in the tumor and interface were quantified. Programmed death-ligand 1 expression was determined within the tumor, stroma, and interface. Results: Patients with shorter PFS had larger tumors ( P = 0.02), mostly in the pancreas ( P = 0.04). We observed a higher mean expression of CD3 +, CD8 +, programmed death-1 + cells, and indoleamine 2, 3-dioxygenase at the interface compared with the tumor: log 10 mean differences 0.56 (95% confidence interval [CI], 0.43–0.68; P < 0.0001), 0.45 (95% CI, 0.32–0.59; P = 0.0002), 0.50 (95% CI, 0.40–0.61; P < 0.0001), and 0.24 (95% CI, 0.03–0.46; P = 0.046), respectively. Patients with longer PFS had higher intratumoral CD3 + T cells, log 10 mean difference 0.38 (95% CI, 0.19–0.57; P = 0.004). Programmed death-ligand 1 expression tended to be higher among patients with shortened PFS (odds ratio, 2.00; 95% CI, 0.68–5.91). Conclusions: Higher intratumoral CD3 + T-cell infiltrate was associated with longer PFS after resection. Abstract : Supplemental digital content is available in the text.